Average Error: 0.0 → 0.0
Time: 12.7s
Precision: 64
$\left(1 \cdot f - t\right) \cdot begin + t \cdot end$
$\left(1 \cdot f - t\right) \cdot begin + t \cdot end$
\left(1 \cdot f - t\right) \cdot begin + t \cdot end
\left(1 \cdot f - t\right) \cdot begin + t \cdot end
double f(double f, double t, double begin, double end) {
double r1843759 = 1.0;
double r1843760 = f;
double r1843761 = r1843759 * r1843760;
double r1843762 = t;
double r1843763 = r1843761 - r1843762;
double r1843764 = begin;
double r1843765 = r1843763 * r1843764;
double r1843766 = end;
double r1843767 = r1843762 * r1843766;
double r1843768 = r1843765 + r1843767;
return r1843768;
}

double f(double f, double t, double begin, double end) {
double r1843769 = 1.0;
double r1843770 = f;
double r1843771 = r1843769 * r1843770;
double r1843772 = t;
double r1843773 = r1843771 - r1843772;
double r1843774 = begin;
double r1843775 = r1843773 * r1843774;
double r1843776 = end;
double r1843777 = r1843772 * r1843776;
double r1843778 = r1843775 + r1843777;
return r1843778;
}

# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(1 \cdot f - t\right) \cdot begin + t \cdot end$
2. Final simplification0.0

$\leadsto \left(1 \cdot f - t\right) \cdot begin + t \cdot end$

# Reproduce

herbie shell --seed 1
(FPCore (f t begin end)
:name "(1.0f - t) * begin + t * end"
:precision binary64
(+ (* (- (* 1 f) t) begin) (* t end)))